Enhancing Efficiency: The Use Of Electronic Signatures In Notarial Deed - Siswanta, Anggitariani Rayi Larasati; Pambudi, Lintang Ario; Kupita, Weda; Wakhid, Nur; Legowo, Pramono Suko; Taufiq, Muhammad (Jurnal Idea Hukum, 2024)
The use of electronic signatures for the parties in the notarial deed is still a matter of debate as to whether its validity is recognized or not. In practice, there are still many notaries who in signing a deed by the parties do not use electronic signatures because there is no clear arrangement regarding electronic signatures in notarial deeds. Therefore, the article will focus on the problem of the concept of electronic signatures that are in accordance with the laws and regulations and the validity of the use of electronic signatures in the partij akta. The research method is normative juridical with a statute approach and a conceptual approach. The results of this research are that basically electronic signatures have legal force and legal consequences as long as they meet the requirements regulated in the Electronic Information Electronic Law 2008 (Amendment 2016). However notarial deeds are not allowed to use electronic signatures according to Article 5 of the EIT Law 2008 (Amendment 2016). Notary as state officials must also create efficient public services by following existing technological developments by using electronic signatures to support e-government to create efficient public services. Therefore, the Government must also provide clear legal protection related to electronic signing for the parties in the notarial deed, mainly in the Notary Law and EIT Law.